Implementasi Pelayanan Bimbingan Konseling Islami terhadap Adaptasi Peserta didik SMA MTA Surakarta Berbasis Boarding School - Arifah, Muthi’ah; Nur Khotimah, Isnaini; Rahmawati, Putri; Widiana Nariswari, Safira; Shobabiya, Mahasri (DAWUH : Islamic Communication Journal, 2023)
The adaptation of students in the boarding school environment is the ability to live independently and fairly, so that they feel satisfied with themselves and their environment. Adaptability in the dormitory environment can be possessed if students have lived a few days in the dormitory. Of course, not only academic knowledge is gained, but even more so learning about life sciences. Many factors affect the adaptation of students in school such as gender, regional background (culture) and grade level. This study aims to determine the implementation of counseling guidance carried out to improve the adaptation of students living in dormitories, especially new grade 10 students. This research uses qualitative methods, where the data search process uses interview techniques. The results of this study show the role of counseling guidance on the adaptation of MTA Surakarta High School students in the form of counseling guidance stages that are applied by identifying problems and needs, making diagnoses, establishing prognosis, providing assistance, evaluating and following up.